Król Maciuś Pierwszy, the Polish Novel for Children Most Often Translated into English - Borodo, Michał (Porównania, 2021)
The article is an attempt to shed light on the history of the Polish novel for children with the highest number of English translations. It is an attempt to explain, with selected examples which have not been discussed so far, how Korczak’s translatorshave dealt with the text of Król Maciuś Pierwszy [King Matt the First], using different translation strategies. The analysed material deserves attention not only because it has so far remained terra incognita of Polish translation studies, but also because each of the translators has accentuated different layers of meaning of the original, modifying it in terms of style, linguistic organization and cultural references.